2020
DOI: 10.1002/jsfa.10223
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of streptococcal biofilm formation by Aronia by extracellular RNA degradation

Abstract: BACKGROUND: The accumulation of oral bacterial biofilms is one of the primary etiological factors for oral diseases. Aronia melanocarpa extracts display general health benefits, including antimicrobial activities. This study evaluates the inhibitory effect of Aronia juice on oral streptococcal biofilm formation.RESULTS: Exposure to 1/10-diluted Aronia juice for 1 min significantly decreased in vitro streptococcal biofilm formation (P < 0.001). No remarkable difference was noted in streptococcal growth by Aroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Regarding other important studies from the scientific literature, a recent study showed that black chokeberry leaf extract also possesses bacteriostatic properties, with S. aureus, Brochothrix thermosphacta, and Salmonella enterica being the most sensitive to the leaf extract compared to Listeria monocytogenes, which was found to be the most resistant bacteria to the back chokeberry leaf extract [52]. A recent study published this year by Lee et al reported that the juice can inhibit the development of an oral streptococcal biofilm at the beginning of its formation by decomposing the formation of extracellular RNA, a structure with a pivotal role in the formation of bacterial biofilms [53]. It seems that the active compounds of black chokeberry (such as flavons, flavonols, flavans, iso/neo-flavonoids, chalcones, and dihydroflavonols) have antibiofilm activity without any toxicity toward the studied species, a beneficial property that lowers the risk of developing resistance, as the current antimicrobials do [4].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other important studies from the scientific literature, a recent study showed that black chokeberry leaf extract also possesses bacteriostatic properties, with S. aureus, Brochothrix thermosphacta, and Salmonella enterica being the most sensitive to the leaf extract compared to Listeria monocytogenes, which was found to be the most resistant bacteria to the back chokeberry leaf extract [52]. A recent study published this year by Lee et al reported that the juice can inhibit the development of an oral streptococcal biofilm at the beginning of its formation by decomposing the formation of extracellular RNA, a structure with a pivotal role in the formation of bacterial biofilms [53]. It seems that the active compounds of black chokeberry (such as flavons, flavonols, flavans, iso/neo-flavonoids, chalcones, and dihydroflavonols) have antibiofilm activity without any toxicity toward the studied species, a beneficial property that lowers the risk of developing resistance, as the current antimicrobials do [4].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to 1/10 diluted chokeberry juice for one minute significantly reduced S. mutans biofilm formation in vitro without affecting streptococcal growth [30]. One week of oral rinse with diluted chokeberry juice led to significantly fewer salivary streptococcal CFUs than rinsing with water.…”
Section: Chokeberrymentioning
confidence: 90%
“…One week of oral rinse with diluted chokeberry juice led to significantly fewer salivary streptococcal CFUs than rinsing with water. Lee and coworkers concluded that the juice might inhibit initial biofilm formation by decomposing extracellular RNA [30]. When chokeberry extracts, subfractions, and compounds were tested for their potential to prevent biofilm formation and inhibit bacterial growth of Escherichia coli and Bacillus cereus, the 50% ethanolic extract was more potent than other extracts.…”
Section: Chokeberrymentioning
confidence: 99%
“…Streptococcus sanguinis harbors a small RNA, cia-dependent RNA, or csRNA, which inhibits the expression of Type IV pilus and retards biofilm formation ( Ota et al., 2018 ). Interestingly, a recent work investigated the role of Aronia melanocarpa juice in the degradation of extracellular RNA, which can control biofilm formation by streptococcus in the oral cavity ( Lee et al., 2020 ).…”
Section: Biofilm Regulation By Non-coding Rna In Gram-positive Bacteriamentioning
confidence: 99%